Wajib Militer Dalam Konteks Pertahanan Negara Dan Undang-Undang Dasar 1945 - Tulus Mampetua Lumban Gaol; Irwan Triadi (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
Compulsory Military Service has become the focal point of debate in the latest National Resource Empowerment Law (PSDN). Some argue that national defence, which forms the basis of compulsory military service, should not be confined solely to military contexts. However, on the other hand, many believe that a military approach is integral to national defence. The author employs a legal and national defence analysis to comprehend the conception of compulsory military service. The findings of the author's research indicate that mandatory military service is a mandate of the law and not voluntary, leaning towards a militaristic approach. Furthermore, the author asserts that all non-militaristic forms of national defense are valid, but a militaristic approach remains obligatory.